Extension Agents’ Use and Acceptance of Social Media: The Case of the Department of Agricultural Extension in Bangladesh - Md Karmruzzaman; Ataharul Chowdhury; Annemarie van Paassen; Wayne Ganpat (Journal of International Agricultural and Extension Education, 2018)
Information and Communication Technologies (ICTs) have been considered as key driving forces for enabling agricultural development ‒the sector which provides livelihoods for majority ofthepopulation in Bangladesh. The Department of Agricultural Extension (DAE), the largest public sector agricultural extension service provider in Bangladesh, hasrecently enactedanew organizational policy for its staffs to use ICTs such as social media to provide better services. However, there is little or merely anecdotal evidence about how extension agents of DAE have been accepting and using social media for their professional work. Drawing onthetheoretical underpinnings of the Technology Acceptance Model (TAM),thisstudy is a first attempt to investigate social media use and acceptance amongextension agents in Bangladesh. Data wascollected using semi-structuredquestionnairesfrom 140 extension agents of DAE who work in the eastern region of Bangladesh. Both descriptive and inferential statistics were used to analyze the data. The findings indicate that most extension agents (51.4%) used social media forhalf an hour to one hour every day. Perceived ease of use (PEoU)andPerceived usefulness (PU) are the most influential elements that determine DAE staff acceptance ofsocial media for performing professional functions. Social media was perceived by extension agents as a means for improving professional performance, such asdisseminating agricultural information;garnering support fornew agricultural policy;networking with clients and colleagues and enabling coordinationof services provided by colleagues. Overall, the findings indicate potential usesof social media in an ICT-based agricultural development strategy in Bangladesh
Keywords: social media; agricultural extension workers; Department of Agricultural Extension; ICTs; communications